Dagusibu, P3K (Pertolongan Pertama Pada Kecelakaan) di Rumah dan Penggunaan Antibiotik yang Rasional di Kelurahan Nusukan - Ika Purwidyaningrum; Jason Merari Peranginangin; Mardiyono Mardiyono; Jamilah Sarimanah (Journal of Dedicators Community, 2019)
The purpose of the service activity is to provide information and education to the public about dagusibu, P3K at home and rational use of antibiotics. Health counseling is needed by the community because it is known that the community. The GKSO Movement (Conscious Family Movement) is a program launched by the Indonesian Pharmacists Association (IAI) which is an effort to improve public understanding of medicines through dissemination of medicines, Dagusibu (Get, Use, Save and Dispose) medical equipment, medicine first aid treatment, and knowledge of antibiotics. The service partner, a resident of RT 08 RW 14, lacks awareness in maintaining cleanliness and still does not know the symptoms caused by an illness. The results of dedication show that citizens gain new knowledge and understand the material provided as a purpose of service